A prospective observational study of prescription pattern in a tertiary care teaching hospital of Jharkhand - Kumari, Abha; Kumar, Keshav; Gari, Manju; Pallavi, Kumari; Choudhury, Subhankar (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Prescription error and irrational prescribing are the avoidable problems imposed on health care delivery system from prescriber side which must be addressed. Periodic prescription audit helps to curtail the error and irrational prescribing. Methods: A prospective observational study was conducted on patients visiting various Outpatient Department of RIMS, Ranchi, Jharkhand on all working days at 11:00 AM to 12:00 PM from 1 August 2018 to 31 July 2019. Various aspects of collected prescriptions were analyzed by using World Health Organization (WHO) prescribing indicators. Results: In this study, out of 700 prescriptions collected, 76 were excluded. Out of total 624 patients analyzed, 382 (61.28%) were male and 242 (38.72%) were female. 48 (7.69%) patients belonged to ≤18, 464 (74.36%) to 19-64 and 112 (17.95%) to ≥65 years of age group. Tablet (71%) was the most common dosage form. None of prescriptions were having registration number of the doctor. 242 (38.78%) prescriptions did not have a diagnosis duly written. The total no. of drugs prescribed in 624 prescriptions was 2176. Only 32 (5.13%) prescriptions were found to have medicines prescribed in block letters. Antibiotics (29%) were the most common class of drugs prescribed. Average number of drugs per prescription was 3.47. Only 48 (2.20%) drugs were prescribed by their generic name while total of injectables prescribed were 102 (4.68%). Total number of drugs from NLEM was 848 (38.97%). 196 (9.00%) drugs were fixed-dose combination. Conclusions: In our study, we found deficiencies in various parts of prescriptions. Prescribing pattern was not in accordance with WHO recommendation for prescribing practice.